Imaging and the Use of Scores for the Diagnosis of Appendicitis in Children - Dingemann, Jens; Ure, Benno (European Journal of Pediatric Surgery, 2012)
The optimal imaging method for diagnosing appendicitis remains unclear. Currently, ultrasound and computed tomography are utilized most often, and data on the use of magnetic resonance imaging are encouraging. However, data on the accuracy of these imaging modalities are contradictory and generally accepted recommendations are lacking. Scoring systems were introduced to improve diagnostic accuracy, but their use also remains controversial. In this review, we focus on the most recent data regarding the advantages and disadvantages of the available imaging techniques and the two primary scoring systems (Alvarado score and Pediatric Appendicitis score) in children with suspected appendicitis.
Keywords: appendicitis; ultrasound; computed tomography; score; children